Answer:
z ≈ 9.22
Step-by-step explanation:
Given the equations
2x-4y+4z-6w=4 ................ 1
6w-4x+4y-4z=-12 ...............2
6w+4x-2y+6z=64 ............... 3
4z+2w+6y-4x=56 ................ 4
We will first need to reduce the equation by cancelling out some variables.
Add equations 1 and 2 will give;
(2x-4x)+(-4y+4y)+(4z-4z)+ (-6w+6w) = 4+12
-2x +0 = 16
-2x = 16
x = -8
Also, equation 2 minus 3
6w-6w+(-4x-4x)+4y+2y+(-4z-6z) = 12-64
-8x+6y-10z = -52
-8(-8)+6y-10z = -52
64+6y-10z = -52
6y-10z = -52-64
6y-10z = -116
3y-5z = -58 ... 5
Equation 3 * 1 and eqn 4 * 3
6w+4x-2y+6z=64 ............... 3
4z+2w+6y-4x=56 ................ 4
6w+4x-2y+6z=64
12z+6w+18y-12x= 168
Subtracting both equations;
16x-20y-6z = -104
8x-10y-3z = -52
8(-8)-10y-3z = -52
-64-10y-3z = -52
-10y-3z = -52+64
-10y-3z = 12 ....... 6
equating 5 and 6 and solving simultaneously;
3y-5z = -58 ... 5 * 10
-10y-3z = 12 ....... 6 * 3
30y-50z = -580
-30y-9z = 36
Add both equations
-50z-9z = -580+36
-59z = -544
z = -544/-59
z = 9.22
Hence z ≈ 9.22